Robustness of plastic scintillation microspheres in the continuous measurement of different river waters. (August 2016) - Tarancón, A.; Novella, O.; Batlle, M.; Pujadas, M.; Cros, J.; García, J.F.
Abstract: Plastic scintillation microspheres (PSm) represent one of the most promising options for monitoring alpha and beta radioactivity in river water. For that reason, a study of the stability of PSm packed into a cell against the continuous flow of river water with different degrees of turbidity was performed over a period of 100 h. The results showed that the volume of the cell became stable after 15 h of pumping and continued to be stable throughout the 100 h of the experiment. During this period of time, the detection efficiency of the PSm, in terms of efficiency*volume, presented mean values of 0.75(3)% for 3 H and 272(11)% for 90 Sr/ 90 Y. No dependence on flow time or river water type was observed. The background was also constant for 100 h and for the different water types, although 222 Rn should be removed from the water beforehand to prevent its accumulation in the PSm. Since PSm did not present any degradation throughout the whole experiment, PSm can undoubtedly be used for monitoring radioactivity with low reagent consumption, low waste generation and low maintenance costs. Highlights: The robustness of PSm to the continuous pass of three river waters was evaluated. The PSm presented robust behaviour for 100 h of continuous flow (25–50 days of monitoring). 3 H and 90 Sr/ 90 Y efficiencies and quenching parameter were constant and had very low variability. The background presented stable behaviour, although 222 Rn should be removed previously.